Keberagaman Semu dan Dilema Minoritas di Kota Banda Aceh - Fasya, Teuku Kemal (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2021)
This study examines the understanding of the concept of diversity (pluralism and multiculturalism) in the city of Banda Aceh; the capital city of Aceh Province which is now more than 800 years old. Can the city be classified as a diversity-friendly city as it is embedded for Pematang Siantar, Manado, Kupang, or Bali, which are among the most diversity friendly regions and are tolerant to other religions and beliefs? This study adopts socio-qualitative with an ethnographic approach to present arguments about the diversity in the city of Banda Aceh. The analytical instrument seeks to empathize with Banda Aceh's value of inductivity, as well as its "particularistic" dimension so that it can be understood emphatically. This article seeks to test the hypothesis of whether or not Banda Aceh City government has sufficiently promoted the culture of minority groups, not only protecting them from violence and granting the right to live and do business. By using observation and in-depth interview techniques, this paper also shows the enigmatic side of minority groups, including the exclusion of â€œsubalternâ€ groups: the weakest minority and can be called the minority of the minorities. The most apparant of this minority group is the Chinese gets a wider portion of the discussion, compared to other minorities. This is because of the complexity that this community enjoys which shapes their lives with other minority groups and builds the concept of encounters with local communities in Banda Aceh. The diversity values of this city experienced a dynamic change. In the last fifteen years, the diversity was best promoted in the city of Banda Aceh during the governance period of Mawardy Nurdin who served as mayor of Banda Aceh from 2007-2014.